PENGARUH PEMBERIAN KREDIT USAHA RAKYAT TERHADAP PERKEMBANGAN USAHA NASABAH BANK RIAU KEPRI SYARIAH KCU PEKANBARU) - Wiyati, Rita; Salmiah, Neneng; Syafirah, Syafirah; Al Amin, Al Amin (Jurnal Daya Saing, 2024)
People's Business Credit is one of the government's efforts to develop the productive sector, especially by helping business actors to obtain financing through the People's Business Credit program, also applies at BRK Syariah by offering various loan products for individuals, businesses or companies. BRK Syariah provides financing facilities intended for micro and small businesses. In developments over the last five years, the disbursement of the People's Business Credit funds has fluctuated, this certainly affects the development of small businesses This research aims to determine the effect of providing people's business credit on the business development of BRK Syariah Pekanbaru customers. Data sources with primary and secondary data, data analysis used is quantitative data. The data analysis technique used is quantitative descriptive. The research results show that the provision of people's business credit has a significant and positive influence on the development of customers' businesses as evidenced by the calculated t value (13,794) > t table (2,021). With a regression value of Y= 1.267 + 0.919X with an R Square value of 84.5%. Keywords: Business Development, People's Business Credit